A Case Report: Successful Management of an Aortic Saddle Embolism in a 28-Year-Old Female - Belotte, Jim; Nicholai, Stephens; Scott, Paul; Barrett, Leonard O.; Faust, Glenn (International Journal of Angiology, 2015)
The obstruction of blood flow at the aortic bifurcation by an embolus defines aortic saddle embolism (ASE). This rare entity occurs preferentially in individuals with cardiovascular diseases such as the middle aged and the elderly. Conversely, its occurrence is sporadic in younger patients. As a result, the diagnosis of ASE is often overlooked or delayed in this age group; therefore, putting these patients at significant risk of neurologic impairment and potential limb loss. Following an extensive literature review, we have found only one reported case of ASE in a patient younger than 30 years. This patient died within 24 hours of admission and was diagnosed with ASE at autopsy. Here, we report for the first time, a case of a successful management of an ASE in a 28-year-old female who presented at our emergency room with acute weakness and numbness of the lower extremities. After vascular consult, the diagnosis of ASE was made and the patient was treated successfully. A week later, the patient was discharged home in stable condition without complications. The purpose of this report is to raise awareness about this potentially fatal condition and emphasize the importance of rapid assessment and treatment. The treatment options are heparin infusion, thrombolytic therapy, and embolectomy.
Keywords: aortic saddle embolism; embolectomy; thrombolytic; adult polycystic kidney disease